Multifocal white matter lesions associated with the D313Y mutation of the α-galactosidase A gene. - Malte Lenders (Public Library of Science (PLoS), 2013)
White matter lesions (WML) are clinically relevant since they are associated with strokes, cognitive decline, depression, or epilepsy, but the underlying etiology in young adults without classical risk factors still remains elusive. Our aim was to elucidate the possible clinical diagnosis and mechanisms leading to WML in patients carrying the D313Y mutation in the α-galactosidase A (GLA) gene, a mutation that was formerly described as nonpathogenic. Pathogenic GLA mutations cause Fabry disease, a vascular endothelial glycosphingolipid storage disease typically presenting with a symptom complex of renal, cardiac, and cerebrovascular manifestations. We performed in-depths clinical, biochemical and genetic examinations as well as advanced magnetic resonance imaging analyses in a pedigree with the genetically determined GLA mutation D313Y. We detected exclusive neurologic manifestations of the central nervous system of the "pseudo"-deficient D313Y mutation leading to manifest WML in 7 affected adult family members. Furthermore, two family members that do not carry the mutation showed no WML. The D313Y mutation resulted in a normal GLA enzyme activity in leukocytes and severely decreased activities in plasma. In conclusion, our results provide evidence that GLA D313Y is potentially involved in neural damage with significant WML, demonstrating the necessity of evaluating patients carrying D313Y more thoroughly. D313Y might broaden the spectrum of hereditary small artery diseases of the brain, which preferably occur in young adults without classical risk factors. In view of the existing causal therapy regime, D313Y should be more specifically taken into account in these patients.